Effects of salbutamol on the inflammatory parameters and angiogenesis in the rat air pouch model of inflammation - Tahereh Eteraf-Oskouei; Arezu Akbarzadeh-Atashkhosrow; Milad Maghsudi; Moslem Najafi (Wolters Kluwer Medknow Publications, 2017)
In the present study, effects of salbutamol on the inflammatory parameters, angiogenesis, interleukin-1 beta (IL-1β) and vascular endothelial growth factor (VEGF) levels were investigated in an air pouch model of inflammation. Inflammation was induced by intrapouch administration of 1% solution of sterile carrageenan in male Wistar rats. Salbutamol (125, 250 and 500 µg/rat) and salbutamol (500 µg/rat) plus propranolol (100 μg/rat) were injected intrapouch. After 6 and 72 h, fluid inside the pouches was collected to measure volume of exudates, leukocytes number and IL-1β levels. To determine angiogenesis, the granulation tissues were dissected out and weighed 3 days after carrageenan injection, then hemoglobin concentration was assessed using a hemoglobin assay kit. In addition, amount of VEGF in the exudates was measured 72 h after induction of inflammation. Leukocyte accumulation and the volume of exudates were significantly inhibited by salbutamol administration. In addition, salbutamol decreased the production of VEGF and IL-1β. Moreover, all used doses of salbutamol significantly inhibited angiogenesis. Interestingly, effects of salbutamol on the attenuation of angiogenesis and inflammatory parameters was similar to diclofenac sodium. Co-administration of propranolol with salbutamol clearly reversed anti-inflammatory effects of salbutamol. Salbutamol can decrease acute and chronic inflammation by β2-adrenergic receptors activation. The observed IL-1β and VEGF inhibitory properties of salbutamol may be responsible for anti-inflammatory and anti-angiogenic effect of the agent.